Colonial Deindustrialisation of India: A Review of Drain Theory. (March 2017) - Mishra, Brijesh K.; Rastogi, Siddhartha
While it is quite well accepted that the British rule imposed a heavy cost on India in terms of financial and industrial losses, the economic impact of the Company rule is still far from settled. Rule of the British East India Company (BEIC), and later the crown, has the scholars divided on whether the colonial India suffered a systematic draw down of its economic resources—the so-called drain theory. While the British version underplays or denies such a drain, the nationalists suggest it was a major long-term damage. This article reviews and critiques the economic policies of the British Raj in detail to know whether there was at all a drain of resources out of India and, if yes, to what extent. It was found that while the nationalists exaggerated effects of the drain, their arguments hold significant value. Finally, drain theory is assessed in the backdrop of the theory of unequal exchange.